Volatile compounds profile of Bromeliaceae flowers - de Souza, Everton Hilo (2016)
Volatile compounds play a vital role in the life cycle of plants, possessing antimicrobial and anti-herbivore activities, and with a significant importance in the food, cosmetic, chemical, and pharmaceutical industry. This study aimed to identify the volatile compounds emitted by flowers of thirteen species belonging to four genera of Bromeliaceae, using headspace solid-phase micro-extraction and detection by gas chromatography-mass spectrometry. A total of 71 volatile compounds belonging to nine chemical groups were identified. The compounds identified represented more than 97 % of the major components in Aechmea bicolor, Ae. bromeliifolia, Ae. distichantha, Ae. fasciata, and Vriesea friburgensis. In the Ananas varieties, over 99 % of the components were identified, and around 90 % in V. simplex. V. friburgensis presented the largest diversity of volatiles with 31 compounds, while Alcantarea nahoumii presented only 14. All three Ananas varieties presented the same 28 compounds in relatively similar abundance, which has been confirmed by principal component analysis. Current taxonomy and pollination syndrome studies available can adequately explain the variation in volatile compounds among species.